If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + m + 18 = 31 Reorder the terms: 18 + m + m = 31 Combine like terms: m + m = 2m 18 + 2m = 31 Solving 18 + 2m = 31 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2m = 31 + -18 Combine like terms: 18 + -18 = 0 0 + 2m = 31 + -18 2m = 31 + -18 Combine like terms: 31 + -18 = 13 2m = 13 Divide each side by '2'. m = 6.5 Simplifying m = 6.5
| 243g^2+54g+3=0 | | 61*ln(y)=13 | | 4/3p=9/8 | | 5(2x-6)=25 | | 2(p+9)= | | 4x-3y+z=4 | | 4x+3(2-3x)=40 | | 3x=5+2(3+1x) | | 3(x+3)-3=7(x+1)-4x | | x^3+2x^2+x= | | (x-1)(-6x+6)= | | 7x-5(x+1)+9=19 | | -16.49(4)+5.2= | | ln(5x-13)=4 | | y(2y-8)=0 | | 3(7Y)= | | 5.4(3+2x)-4.2=12 | | 5(x-1)+3(2x-1)=3 | | 4.17x+0.94=3.7x | | 1.7(-9.7x+6)-5= | | 0.1x+0.3= | | 6x-5-1+2x-4x=66 | | 7x-8x+x-5x= | | F=(1.8*-5)+32 | | 32x=456 | | 1.5x-3=-1.5x+15 | | 4v-18=6(v-4) | | -5a-2=3(a-6) | | 760-50h=0 | | -9.7(1.7x-5)+6= | | .16x+.8(x-4)=.01(3x-2) | | 3+2x=2(2x+2)-3(x-3) |